1997
DOI: 10.1021/bi970090t
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Multiple Mechanisms for Membrane Binding and Integration via Carboxyl-Terminal Insertion Sequences

Abstract: Subcellular localization of proteins with carboxyl-terminal insertion sequences requires the molecule be both targeted to and integrated into the correct membrane. The mechanism of membrane integration of cytochrome b5 has been shown to be promiscuous, spontaneous, nonsaturable, and independent of membrane proteins. Thus endoplasmic reticulum localization for cytochrome b5 depends primarily on accurate targeting to the appropriate membrane. Here direct comparison of this mechanism with that of three other prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 47 publications
(84 reference statements)
5
104
0
Order By: Relevance
“…We have previously demonstrated that this fusion protein inserts into microsomal membranes in vitro (Kim et al, 1997) and that a Bcl-2 fusion protein that contains the cytochrome b5 insertion sequence is speci®cally targeted to the ER in Rat ®broblasts, and is functional (Zhu et al, 1996). However, Rat2 ®broblasts expressing the mT/cb5 fusion protein behind an inducible MMTV promoter did not display the early morphologic changes suggestive of transformation that we noted in mT expressing cells (Taylor, Zhu and Andrews, unpublished).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…We have previously demonstrated that this fusion protein inserts into microsomal membranes in vitro (Kim et al, 1997) and that a Bcl-2 fusion protein that contains the cytochrome b5 insertion sequence is speci®cally targeted to the ER in Rat ®broblasts, and is functional (Zhu et al, 1996). However, Rat2 ®broblasts expressing the mT/cb5 fusion protein behind an inducible MMTV promoter did not display the early morphologic changes suggestive of transformation that we noted in mT expressing cells (Taylor, Zhu and Andrews, unpublished).…”
Section: Resultsmentioning
confidence: 73%
“…Thus it is possible that mT mediates some cytoskeletal rearrangements via interactions with these molecules from the perinuclear location. Furthermore, the insertion of mT into the relevant membrane that is necessary for transformation may be dependent upon the interaction of the mT complex with cytoskeletal elements (Andrews et al, 1993;Kim et al, 1997).…”
Section: Mechanism Of Middle-t Mediated Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3A (lanes 1 to 3, þ mbs) shows that Cb5-A and Cb5-D, as well as the control ER TA proteins rat Cb5 (Janiak et al, 1994a;Kim et al, 1997) and rat vesicle-associated membrane protein 2 (Vamp2) (Kim et al, 1999), bound ER membranes in a posttranslational manner, as evidenced by their recovery in bottom fractions of step gradients after centrifugation. By contrast, only a small amount of each of these proteins (O) to (Q) Expressed Cb5-A (O) and endogenous mitochondrial E1b (P) in a portion of a BY-2 cell.…”
Section: In Vitro Insertion Of Cb5 Proteins Into Er and Mitochondrialmentioning
confidence: 99%
“…By contrast, only a small amount (5%) of Cb5-A was recovered with mitochondria. The lack of Cb5-A targeting to mitochondria in vitro was surprising because other Cb5 proteins, including the ERspecific rat Cb5 used as a control ( Figure 3B, lane 3, þ mbs), are known to insert spontaneously into mitochondria and other membrane systems, including liposomes, in vitro (Remacle, 1978;Enoch et al, 1979;Kim et al, 1997). A soluble rat preornithine carbamyl transferase-Protein A fusion (pOCTgPA), which is known to be translocated into the mitochondrial matrix (Janiak et al, 1994a), was efficiently (84%) incorporated into mitochondria, as evidenced by processing of the presequence (cleavage) resulting in the formation of a lower molecular mass polypeptide (lane 3, þ mbs).…”
Section: In Vitro Insertion Of Cb5 Proteins Into Er and Mitochondrialmentioning
confidence: 99%